2021
DOI: 10.21203/rs.3.rs-139931/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of PTSD Symptoms Among Psychiatric Patients During the COVID-19 Pandemic

Abstract: Background: The outbreak of the COVID-19 pandemic has caused extensive public health concern and posed great challenges to the medical services, including the mental health concern for psychiatric patients who were one of neglected groups. The current study aimed to assess the prevalence and risk factors of post-traumatic stress disorder (PTSD) symptoms among psychiatric patients in China during the pandemic. Method: Self-reported questionnaires were distributed to psychiatric patients in several psychiatric h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In concordance with previous research on COVID‐19 and other outbreaks of infectious disease, we found evidence that traumatic stress symptoms were associated with younger age (Karatzias et al, 2020 ) lower‐income, and financial worries. Consistent with most previous studies, we found evidence of an association between lower levels of perceived social support and traumatic stress symptoms (Boyraz & Legros, 2020 ) but this contrasts with a study of psychiatric patients in China during the pandemic, which failed to find an association (Tang et al, 2021 ). Previous studies that investigated associations between COVID‐19‐related traumatic stress symptoms and gender, physical health and risk of severe infection, and key worker status reported mixed findings and we found no evidence of such associations in our study.…”
Section: Discussionsupporting
confidence: 84%
“…In concordance with previous research on COVID‐19 and other outbreaks of infectious disease, we found evidence that traumatic stress symptoms were associated with younger age (Karatzias et al, 2020 ) lower‐income, and financial worries. Consistent with most previous studies, we found evidence of an association between lower levels of perceived social support and traumatic stress symptoms (Boyraz & Legros, 2020 ) but this contrasts with a study of psychiatric patients in China during the pandemic, which failed to find an association (Tang et al, 2021 ). Previous studies that investigated associations between COVID‐19‐related traumatic stress symptoms and gender, physical health and risk of severe infection, and key worker status reported mixed findings and we found no evidence of such associations in our study.…”
Section: Discussionsupporting
confidence: 84%